Knowledge about epidemiological determinants of obesity and its management amongst medical professionals of Marathwada region of Maharashtra, India - Kausar, Hina M.; Giri, Purushottam A.; Siddiqui, Azhar A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Obesity has become a challenge in medical care worldwide. Medical professionals have a significant role to play in preventing and diagnosing weight problems and in providing initial counseling. Health professionals are poorly prepared in weight management, which has an effect on their knowledge and management skills with regard to overweight and obese patients. Hence the present study was carried out to assess the knowledge about epidemiological determinants of obesity and its management amongst medical professionals of Marathwada region of Maharashtra, India. Methods: A cross-sectional study was carried out during the period of March to April 2019 amongst 110 medical professionals at Department of Community Medicine of IIMSR Medical College, Badnapur, Jalna, Maharashtra, who were actively participated in continued medical education (CME) on obesity and its management where the knowledge of medical professionals were assessed. Data was analysed by using appropriate statistical test whenever necessary. Results: In this study, the pre-test good knowledge score was 14 (12.7%), which increased to 61 (55.5%) post CME. The pre-test mean score of level of knowledge was 7.41±4.12 and after CME, it was 12.90±5.21 and the mean difference was 5.49, which was statistically highly significant. Conclusions: As obesity is a public health problem globally, there was marked improvement in the knowledge amongst medical professionals after CME on epidemiological determinants of obesity and its management.